Mediating role of AI adoption between the relationship of leadership vision, change management capability, competitive pressure, trading partnerships, and SME performance - Faizan ul Haq; Norazah Mohd Suki (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2024)
This study investigates the critical drivers of artificial intelligence (AI) adoption in SMEs. The mediating role of AI adoption on the relationship between leadership vision, change management capability, competitive pressure, trading partnerships, and SME performance is also investigated. This research employs a quantitative methodology, collecting data through structured questionnaires from senior and middle-level managers of manufacturing SMEs in Pakistan. Data were analyzed using the software SmartPLS for partial least squares structural equation modeling (PLS-SEM). The results reveal that trading partnerships are the most critical drivers of AI adoption in SMEs within an emerging economy, followed by change management capabilities and leadership vision. These factors contribute to improving SME performance in competitive and resource-constrained markets, aligning with Sustainable Development Goal 9 (industry, innovation, and infrastructure). Additionally, AI adoption mediates the relationship between trading partnerships, competitive pressure, and SME performance. This research uncovers unique insights by integrating the technology-organization-environment (TOE) framework, Resource-based view theory, and diffusion of innovations theory simultaneously in a proposed research framework that tests the critical drivers of AI adoption in SMEs within an emerging economy.
Keywords: 330; AI adoption; SME performance; industry 4.0; competitive pressure; tradingpartnerships; technology-organization-environment (TOE) framework; leadership vision